Formal and informal help-seeking intentions/behaviors among students and workers during the COVID-19 pandemic: a scoping review - Takashi Yamauchi; Takashi Shimazaki; Hiroyuki Yanagisawa; Machi Suka (Komiyama Printing Co. Ltd, 2023)
Background: Students and workers have been subjected to increased levels of psychological distress due to the quarantine policy and containment measures during the COVID-19 pandemic. This scoping review aimed to present an overview of published evidence regarding formal and informal help-seeking intentions/behaviors for non-mental health-related issues as well as mental health-related issues among students and workers during the pandemic. Methods: In June 2022, we searched MEDLINE, APA PsycNet, and CINAHL for articles reporting the state of help-seeking intentions/behaviors among students and workers during the pandemic. Peer-reviewed original articles published in English were selected. Results: In total, 150 articles were identified, and 12 articles were selected for final analysis after removing articles that met the exclusion criteria. Three studies targeted university students, and nine targeted healthcare workers. Study settings were restricted to Western countries and China. Of the 12 studies, 11 were observational and predominantly cross-sectional studies. Two longitudinal studies using student samples suggested that university students became more reluctant to seek help from both formal and informal sources during the COVID-19 pandemic compared to before, despite the increased need for support during the pandemic. Among healthcare workers, the proportions of those who sought help from formal sources in person were low (7-26%), even among those with mental health issues, despite the increase in the need for mental health services. One randomized controlled study reported that a brief video-based intervention increased treatment-seeking intentions among healthcare workers in the intervention group compared with the non-intervention group. Conclusions: The present review revealed that, although most studies included in the final analysis were cross-sectional, intentions/behaviors to seek help from both formal and informal sources decreased among university students, even those with mental health issues. Among healthcare workers, while the frequency of help-seeking from formal sources in person was low, a brief online intervention was suggested to be useful for promoting help-seeking from formal sources. During public health crises such as the COVID-19 pandemic, system and infrastructure development of online help-seeking services could potentially promote formal and informal help-seeking intentions/behaviors for diverse issues, including non-mental health-related issues, among university students and healthcare workers/providers.